Bifurcation of Traveling Wave Solutions of the Dual Ito Equation - Xinghua Fan; Shasha Li (Abstract and Applied Analysis)
The dual Ito equation can be seen as a two-component generalization of the well-known Camassa-Holm equation. By using the theory of planar dynamical system, we study the existence of its traveling wave solutions. We find that the dual Ito equation has smooth solitary wave solutions, smooth periodic wave solutions, and periodic cusp solutions. Parameter conditions are given to guarantee the existence.